El poder papal en el De Renuntiatione Papae de Pedro de Juan Olivi - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Filosofía Alejandro Korn. Sección de Filosofía Medieval., 2001)
The article analyses the first scholarly quaestio on Papal resignation. In this question it was discussed not only the problem of the Papal resignation, but also the grounds of that decision, namely, the Papal sovereignty, a polemic topic for scholars devoted to Medieval political thinking. The author of that quaestio was Peter John of Olivi. The goal of the article is to examine its author's conception of the pontifical plenitudo potestatis, that is, to evaluate the kind of power the Papal authority had and its influence on the ecclesiastical environment, a topic that up to that date had been mainly discussed by canonists and considered only tangentially by the majority of theologians.
Fil: Souza, José Antônio de C.R. de. Universidad Federal de Goiás , Brasil.
Keywords: FILOSOFÍA MEDIEVAL; CLERO; ILESIA Y PODER; PODER POLÍTICO; TEOLOGÍA; PODER ECLESIÁSTICO; ALTA EDAD MEDIA; IGLESIA CATÓLICA; OLIVI, PEDRO DE JUAN OLIVI; QUAESTIO, PEDRO DE JUAN OLIVI